Noncommutative geometry and quantization - Várilly Boyle, Joseph C. (2000)
En el libro: Particles and Fields (Proceedings of the X Jorge André Swieca Summer School, São Paulo, Brazil, Febrero 2000), World Scientific, Singapore, Junio 2000, pp. 321-346.